Kinetic Coefficients for Mixed Adsorbate Fluids in Narrow Pores - Yu.K. Tovbin; A.B. Rabinovich; D.V. Yeremich (Adsorption Science & Technology)
The kinetic coefficients (trace diffusion, mutual diffusion and shear viscosity) of molecules in slit-like and sphero-cylindrical mesoporous systems were studied in terms of the modified lattice-gas model (LGM). The LGM equations were derived for molecules of the mixture having a spherical shape and similar size. A new equation for the velocity of the thermal molecule was used. The theory takes the change in the mechanism of particle migration in different phases into account, viz. from pair collisions for the gas to the overcoming of the activation barrier by thermofluctuation for dense phases. At low mixture densities corresponding to an ideal gas phase, the LGM expression for the mutual diffusion coefficient agrees with the expression of the rigorous kinetic theory of gases. The theory allows the calculation of the kinetic coefficients for the components of binary mixtures in full gas-liquid density areas. The supramolecular structure of the sphero-cylindrical system was modelled by sections with a simple regular geometry (cylindrical and spherical) with the additional inclusion of junctions between different pore sections. The contributions of the near-wall regions caused by the molecule-wall potential to the general appearance of the phase diagrams and the effect of the pore size on the capillary condensation conditions were discussed.